Effects of simulator training on novice operators’ performance in simulated ice covered waters - Power-Macdonald, Stephanie; MacKinnon, Scott; Simões Ré, Antonio; Power, Jonathan; Baker, Andrew (National Research Council Canada, 2011)
Operations in ice-covered waters are increasing as Arctic environments become more accessible. With this move, there is an increased need for better equipment, procedures, regulations and training to operate in cold, harsh environments. No mandatory training exists for lifeboat coxswains charged with navigating lifeboats in ice-covered water during emergency evacuation situations. This study sets out to examine simulator training in comparison with traditional coxswain training to observe performance in a simulated ice field. Participants completed one of three training regimes before performing a standardized protocol of lifeboat maneuvers within a simulated ice-field. Performance measurements and psychometric measurements were collected. Simulator trained participants were 3.35 times more likely to correctly navigate through the course compared to those who received standard training. As well, simulator trained participants perceived a higher level of confidence and proficiency towards their past and future performance. Future work in this area should further examine the effect simulator training could have in real ice environments.